Präventionsdilemma auf kommunaler Ebene? - Herbert-Maul, Annika; Abu-Omar, Karim; Till, Maike; Fleuren, Tobias; Wolff, Andrea R.; Reimers, Anne Kerstin (Prävention und Gesundheitsförderung, 2022)
Health promotion often benefits mainly socially privileged persons, while disadvantaged people are reached less often. It remains an important question whether the same holds true for the recruitment of communities to take part in health promotion projects. Objectives Based on two Bavarian projects for community-based physical activity promotion, this study examines whether socioeconomically disadvantaged communities with low health promotion structures are being reached to apply for project funding and which factors influence their readiness to participate. Methods Data on population level indicators and socioeconomic disadvantages of 171 communities are compared for participating/interested communities and disadvantaged communities. By means of a systematic internet search, health promotion activities of selected communities are analyzed. Barriers and facilitating factors for the implementation of the two projects are recorded through a document analysis. Results The participating and interested communities have larger populations, are less disadvantaged, and provide more health promotion offers than disadvantaged communities. Financial factors, political support, and committed leadership have a large influence on participation. Discussion The results of this study point to an inequality paradox for preventive actions on the community level. In order to prevent health inequalities between communities, disadvantaged communities might need to be involved in the design of funding programs in order to tailor these programs to their needs and thus make it easier for them to acquire project fundin
Keywords: Background; Community-based health promotion; Community readiness; Socioeconomic deprivation; Funding programs; Participation